2020
DOI: 10.1002/anie.202001388
|View full text |Cite|
|
Sign up to set email alerts
|

Thiol–Anhydride Dynamic Reversible Networks

Abstract: Supporting information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…Dynamic covalent bonding features reversible covalent bond breaking and formation with external stimuli, such as light, temperature, mechanical stress, etc 63–68 . According to a previous review, 65 several covalent bonds, including CC, CN, CO, SC, SS bonds, have been reported to undergo reversible dynamic covalent bonding exchanges.…”
Section: Covalent Adaptable Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic covalent bonding features reversible covalent bond breaking and formation with external stimuli, such as light, temperature, mechanical stress, etc 63–68 . According to a previous review, 65 several covalent bonds, including CC, CN, CO, SC, SS bonds, have been reported to undergo reversible dynamic covalent bonding exchanges.…”
Section: Covalent Adaptable Networkmentioning
confidence: 99%
“…Dynamic covalent bonding features reversible covalent bond breaking and formation with external stimuli, such as light, temperature, mechanical stress, etc. [63][64][65][66][67][68] According to a previous review, 65 several covalent bonds, including C C, C N, C O, S C, S S bonds, have been reported to undergo reversible dynamic covalent bonding exchanges. Because of this feature, significant efforts have applied dynamic covalent bonding to synthesize two-and three-dimensional covalent molecules with different size, geometry and functionality.…”
Section: Covalent Adaptable Networkmentioning
confidence: 99%
“…To fabricate liquid‐crystalline elastomers capable of thermally stable, permanent retention of phototropic actuation, materials were prepared by using C6M, allyl succinic anhydride–hexane dithiol (ASA‐HDT), and a diarylethene (DAE) diacrylate monomer (Figure 1). The DAE and ASA‐HDT monomers were synthesized following prior reports [22, 34] . Components were mixed at a thiol:acrylate functional group ratio of 1 : 0.75 and 15 wt% DAE monomer.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the abovementioned problems, the latest generation of self-healing glassy thermoset polymers introduce various dynamic covalent bonds within the cross-linked network. The resultant covalent adaptive network can reorganize by thermally or chemically triggering the reversible reactions and thus endowing the polymer with intrinsic multiple self-healing ability and recyclability. The rearrangement and reorganization of covalent adaptive networks heavily depend on both high molecular mobility and high activity of reversible bonds. , The former makes cleaved moieties rapidly find their counterparts, and the latter can accelerate the formation of new bonds.…”
Section: Introductionmentioning
confidence: 99%